Inter- and intra-marriage premiums revisited: It's probably who you are, not who you marry! - Lena Nekby (Institute for the Study of Labor (IZA), 2010)
For immigrants, intermarriage with natives is assumed to have an assimilating role due to the enhancement of local human capital such a union creates in the form of improved knowledge about host country institutions, language and customs as well as access to native spouses' networks and contacts. However, marriage choice is endogenous, unobserved factors influence who we marry and our labor market outcomes. This study uses panel data on immigrants and their spouses in Sweden to estimate marriage premiums taking into account individual heterogeneity. This is done for three types of marriages; intermarriage to natives and intra-marriage with immigrants from home countries or other (non-Swedish) countries. A staggered fixed effects model is estimated separately for each marriage type to further disentangle a causal effect of intermarriage (intra-marriage) on annual income from any remaining positive selection effects into respective marriage type. Results from fixed effects estimation indicate that all types of marriage (with one exception) yield positive marriage premiums of similar magnitude. Significant pre-marriage income growth and a lack of postmarriage income growth for those that marry natives suggest that intermarriage premiums are largely due to selection.
Keywords: J12; J61; F22; 330; intermarriage; intra-marriage; income; immigration; assimilation; gender